Dynamics of the Prophet's Ijtihad: A Reflection of Needs or Limitations? - Sutiyan, Dolly Riri Ramdhanu Jamel (Global Research Network, 2024)
Conceptually, the term ijtihad is an effort to dig out law which had been existed in the Prophet’s live. In its development ijtihad has been done by prophet followers up now. Although in a certain period as so called taklid period, in which ijtihad is not allowed, however, at another period of time ijtihad is allowed. In fact, ijtihad cannot be avoided and it is a must to cope with more complex problems. It is widely understood that not all the result of ijtihad as the renewal of the old one. The fact shows that the result of new ijtihad as similarity or even the same with the old one. Although the result of thenew ijtihad is totally different from the old one, the new one cannot change the status of the old one for there is a rule says that ijtihad cannot be canceled by another ijtihad. Based on the application of ijtihad, the sources of Islamic laws direct Islamic followers to understand them. The sources of Islamic laws admitted and followed by ulama are Holy Qur’an, hadis, ijma and qiyas.